Laser-assisted photoemission from adsorbate-covered metal surfaces: Time-resolved core-hole relaxation dynamics from sideband profiles - Zhang, C.-H.; Thumm, U. (My University, 2009)
Illumination of an adsorbate-covered metal surface with an xuv and a delayed ir laser pulse can result in sidebands in the photoelectron (PE) spectra. We present a theoretical model for the delay-dependent PE spectra and show how the relaxation dynamics of xuv-induced core-level holes in adsorbate atoms can be deduced from the temporal shift between sideband peaks in the spectra of secondary adsorbate (Auger) electrons and conduction-band PEs from the substrate. Furthermore, in comparison with gaseous targets, we find a characteristic sideband-intensity enhancement in the laser-assisted photoemission from the substrate core-level bands. This sideband enhancement effect can be tested in experiments with tunable xuv wavelength. Our calculated PE spectra support time-resolved experiments for Xe-covered Pt(111) surfaces, promoting the direct analysis in the time domain of surface dynamical processes.